2012
DOI: 10.1038/nm.2634
|View full text |Cite
|
Sign up to set email alerts
|

cGMP-Prkg1 signaling and Pde5 inhibition shelter cochlear hair cells and hearing function

Abstract: Noise-induced hearing loss (NIHL) is a global health hazard with considerable pathophysiological and social consequences that has no effective treatment. In the heart, lung and other organs, cyclic guanosine monophosphate (cGMP) facilitates protective processes in response to traumatic events. We therefore analyzed NIHL in mice with a genetic deletion of the gene encoding cGMP-dependent protein kinase type I (Prkg1) and found a greater vulnerability to and markedly less recovery from NIHL in these mice as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 59 publications
8
90
0
Order By: Relevance
“…This Cys-42 is ideally located to modulate the interaction with the RhoA GTPase depending on the redox state of the kinase, with disulfide formation limiting the phosphoactivation and anti-apoptotic signaling the GTPase would otherwise afford in the absence of Cys-42 oxidation. Pharmacological inhibition of PDE5 also protected hair cells from noise-induced cell death and hearing loss (38), perhaps consistent with disulfide activation of PKG I␣ being a generic mechanism of cell death in different cell types.…”
Section: Discussionsupporting
confidence: 54%
“…This Cys-42 is ideally located to modulate the interaction with the RhoA GTPase depending on the redox state of the kinase, with disulfide formation limiting the phosphoactivation and anti-apoptotic signaling the GTPase would otherwise afford in the absence of Cys-42 oxidation. Pharmacological inhibition of PDE5 also protected hair cells from noise-induced cell death and hearing loss (38), perhaps consistent with disulfide activation of PKG I␣ being a generic mechanism of cell death in different cell types.…”
Section: Discussionsupporting
confidence: 54%
“…We also showed that the PDE5 inhibitor vardenafil, which is used for the treatment of erectile dysfunction, dramatically potentiated the anticancer effects of EGCG without affecting normal cells. The clinical value of our findings is appreciable, because PDE5 inhibitors are widely used drugs approved by the FDA for chronic use (36). Hepatotoxicity is the well-known adverse effect of high-dose EGCG (37), and, in some cases, elevation of transaminases ALT/AST has been observed in clinical trials (13).…”
Section: Pde5 Is Overexpressed In Various Types Of Human Cancer and mentioning
confidence: 67%
“…In conclusion, an increasing number of studies have now demonstrated that the counting of IHC ribbons after hearing loss, for example, in aged specimens [62,64] , or after an acoustic trauma [22,31,32,61,75,76] , or after intake of aminoglycoside [77,78] , can be a first indication of the loss of IHC synapses and AN integrity, independent of (elevated) hearing thresholds.…”
Section: Molecular Biomarker For Dissection Of the Ihc Phenotype And mentioning
confidence: 91%